A Lexicometric Analysis of the Poems from O Guardador de Rebanhos - Assunção, Carlos; Araújo, Carla (Acta Scientiarum. Language and Culture, 2019)
This study is guided by a methodology that fits into a research model related to corpus linguistics and it primarily aims at developing a lexicometric analysis of the poems from O guardador de rebanhos, by Alberto Caeiro (Pessoa, 2007), using a computational resource of lexical analysis, the NooJ software (Silberztein, 2015). Based on the linguistic data provided by NooJ, we begin by presenting the general features that characterise the poems from O guardador de rebanhos, then we analyse the list of theme words, departing from the list of tokens in descending order of frequency. In the last part, we present thematic fields, drawn from the theme words of the corresponding poems. The lexicometric analysis of the poems from The keeper of flocks, by Alberto Caeiro (Pessoa, 2007), may be seen as an opportunity for didactic operationalisation in secondary education, revealing NooJ as a potential didactic resource and providing evidence of the indisputable contribution of corpus linguistics to teaching.